Biodiversity of Lactobacillus plantarum from traditional Italian wines - Testa, Bruno (Springer Netherlands, 2014)
In this study, 23 samples of traditional wines produced in Southern Italy were subjected to microbiological analyses with the aim to identify and biotype the predominant species of lactic acid bacilli. For this purpose, a multiple approach, consisting in the application of both phenotypic (API 50CHL test) and biomolecular methods (polymerase chain reaction-denaturing gradient gel electrophoresis and 16S rRNA gene sequencing) was used. The results showed that Lactobacillus plantarum was the predominant species, whereas Lb. brevis was detected in lower amount. In detail, out of 80 isolates 58 were ascribable to Lb. plantarum and 22 to Lb. brevis. Randomly amplified polymorphic DNA-polymerase chain reaction was used to highlight intraspecific variability among Lb. plantarum strains. Interestingly, the cluster analysis evidenced a relationship between different biotypes of Lb. plantarum and their origin, in terms of wine variety. Data acquired in this work show the possibility to obtain several malolactic fermentation starter cultures, composed by different Lb. plantarum biotypes, for their proper use in winemaking processes which are distinctive for each wine.